2014
DOI: 10.2337/db14-0227
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Vessel Calibers Predict Long-term Microvascular Complications in Type 1 Diabetes: The Danish Cohort of Pediatric Diabetes 1987 (DCPD1987)

Abstract: Diabetic neuropathy, nephropathy, and retinopathy cause significant morbidity in patients with type 1 diabetes, even though improvements in treatment modalities delay the appearance and reduce the severity of these complications. To prevent or further delay the onset, it is necessary to better understand common underlying pathogenesis and to discover preclinical biomarkers of these complications. Retinal vessel calibers have been associated with the presence of microvascular complications, but their long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
65
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 42 publications
8
65
2
Order By: Relevance
“…The findings of this study indicated that the 16 year incidence of diabetic peripheral neuropathy was associated with narrower arteriolar calibre, wider venular calibre and lower fractal dimension at baseline [52,53].…”
Section: Retinal Vascular Changes Associated With Diabetic Microvascumentioning
confidence: 59%
See 2 more Smart Citations
“…The findings of this study indicated that the 16 year incidence of diabetic peripheral neuropathy was associated with narrower arteriolar calibre, wider venular calibre and lower fractal dimension at baseline [52,53].…”
Section: Retinal Vascular Changes Associated With Diabetic Microvascumentioning
confidence: 59%
“…In the same study, these associations were also confirmed among patients with type 1 diabetes [61]. In the Danish Cohort of Pediatric Diabetes 1987 (DCPD1987) with type 1 diabetes, wider venular calibre, narrower arteriolar calibre and lower fractal dimension measured at baseline were associated with the development of nephropathy at the 16 year follow-up [52,53].…”
Section: Retinal Vascular Changes Associated With Diabetic Microvascumentioning
confidence: 64%
See 1 more Smart Citation
“…This thesis provides the longest prospective study to date on both retinal vessel calibres (Broe et al 2014a) and retinal fractal dimensions (Broe et al 2014b) and their predictive value on diabetic microvascular complications.…”
mentioning
confidence: 99%
“…Retinal vascular calibres are important non-invasive biomarkers which are predictive of early-stage (Cheung et al 2008) as well as end-stage diabetic retinopathy (Broe et al 2014). However, observations regarding retinal vascular calibres and diabetic macular oedema (DMO) or DMI are still limited.…”
Section: Referencementioning
confidence: 99%